The spectral-luminescent properties of microcrystalline YАl3(ВО3)4 : Се3 +, Tb3 +, obtaining by coprecipitation method - Shevchenko, Gvidona P.; Bokshyts, Yuliya V.; Ivlieva, Irina Y.; Malashkevich, Georgii E.; Kichanov, Sergey E. (Journal of the Belarusian State University. Chemistry, 2018)
YАl3(ВО3)4 : Се3+, Tb3+ microcrystals were synthesized via using colloid-chemical approach. The effect of sensitizing of Tb3+ ion luminescence by Се3+ ions, caused by electronic excitation energy transfer of Се3+ ions from 5d levels to 7Fj levels of Tb3+, was established. The efficiency of such sensitization is about 50 %. With the concentration of Се3+ being the same (1 at. %), doubling the Tb3+ concentration (from 5 to 10 at. %) will cause 10 % increase of sensitized luminescence efficiency of Tb3+.
Keywords: coprecipitation; yttrium aluminium borate; luminescence; sensitization